2007
DOI: 10.1093/eurheartj/ehm358
|View full text |Cite
|
Sign up to set email alerts
|

Outcome parameters for trials in atrial fibrillation: executive summary: Recommendations from a consensus conference organized by the German Atrial Fibrillation Competence NETwork (AFNET) and the European Heart Rhythm Association (EHRA)

Abstract: Atrial fibrillation (AF), the most common atrial arrhythmia, has a complex aetiology and causes relevant morbidity and mortality due to different mechanisms, including but not limited to stroke, heart failure, and tachy- or bradyarrhythmia. Current therapeutic options (rate control, rhythm control, antithrombotic therapy, 'upstream therapy') only prevent a part of this burden of disease. Several new treatment modalities are therefore under evaluation in controlled trials. Given the multifold clinical consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
144
0
28

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(174 citation statements)
references
References 125 publications
2
144
0
28
Order By: Relevance
“…974 Nevertheless, early recurrences have been shown to predict arrhythmia recurrences late after catheter ablation of AF in some patients. 260,329,935,976,977,978 …”
Section: Early Recurrence After Ablationmentioning
confidence: 99%
See 1 more Smart Citation
“…974 Nevertheless, early recurrences have been shown to predict arrhythmia recurrences late after catheter ablation of AF in some patients. 260,329,935,976,977,978 …”
Section: Early Recurrence After Ablationmentioning
confidence: 99%
“…63,974 AF-specific QOL measures, including the AF Effect on QOL (AFEQT) questionnaire, 1095 the Mayo AF Symptom Inventories, 63 and the Arrhythmia-Specific questionnaire in Tachycardia and Arrhythmia (ASTA), 1096 have been developed and are in the process of validation. A recent study reported that disease-specific assessments of QOL are superior to generic questionnaires.…”
Section: Outcomes Of Af Ablation In Populations Not Well Represented mentioning
confidence: 99%
“…As the mean life-span increases, partially as a function of more effective interventional procedures and preventive measures, AF prevalence consequently increases (it is expected to double in the next 50 years) [3,4]. This phenomenon is especially evident in subjects at high CV risk [5] where screening for AF in patients with ischaemic stroke reveals arrhythmia in over 20% of cases [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…One quarter of all 40‐year‐olds will develop this arrhythmia during the course of their lives 3. AF increases the risk of stroke by 5 times4 and doubles the risk of cardiovascular deaths and strokes after just 1 year 5…”
Section: Introductionmentioning
confidence: 99%